One-pot synthesis and enzyme-responsiveness of amphiphilic doxorubicin prodrug nanomicelles for cancer therapeutics. Issue 43 (30th September 2022) - Han, Ling-Na; Wang, Kai-Qiang; Ren, Zi-Ning; Yang, Xue; Duan, Xiao; Krishnan, Sasirekha; Jaisankar, Abinaya; Park, Jeong-Hui; Dashnyam, Khandmaa; Zhang, Wujie; Pedraz, José Luis; Ramakrishna, Seeram; et al.
Abstract : A doxorubicin-based nanomedicine with a one-pot synthesis method and FDA-approved materials could solve the problems of a complicated preparation process and avoid the use of non-FDA-approved materials for clinical use and industrial production. Abstract : In this study, we report a one-pot synthesis and enzyme-responsiveness of polyethylene glycol (PEG) and glutamic acid (Glu)-based amphiphilic doxorubicin (DOX) prodrug nanomicelles for cancer therapeutics. The nanomicelles were accomplished by esterification and amidation reactions. The nuclear magnetic resonance (NMR) and Fourier transform infrared (FTIR) data confirmed the structure of nanomicelles. The DOX-loaded nanomicelles showed a DLS-measured average size of 107 nm and excellent stability in phosphate-buffered saline (PBS) for 7 days. The drug loading and cumulative release rates were measured by ultraviolet-visible (UV-vis) spectrophotometry at 481 nm. The cumulative release rate could reach 100% in an enzyme-rich environment. Further, the therapeutic efficiency of nanomicelles to cancer cells was determined by cell viability and cellular uptake and distribution using HeLa cells. The cell viability study showed that the DOX-loaded nanomicelles could effectively inhibit the HeLa cell proliferation. The cellular uptake study confirmed that the nanomicelles could be effectively ingested by HeLa cells and distributed into cell nuclei. Based on the collective experimental data, this study demonstrated that the synthesized nanomicellar prodrug of DOX is a potential candidate for cancer therapeutics.